The complete genome sequence BK polyomavirus study in kidney transplanted patients - Manoochehr Makvandi; Gholam Abbas Kaydani; Heshmatollah Shahbazian; Alireza Teimoori; Fakher Rahim; Sajjad Aslani (Society of Diabetic Nephropathy Prevention, 2019)
Background: BK polyomavirus is a member of the Polyomaviridae. This virus has spread worldwide and up to 82% of the world populations are serologically positive. BK polyomavirus usually transmits through inhalation or fecal-oral way in childhood, as well as is likely to cause an asymptomatic disease. The virus can be reactivated in people who are immunocompromised. Objectives: In this study we aimed to determine the complete genome sequence of BK polyomavirus in 5 patients receiving kidney transplantation in Golestan hospital, Ahvaz, south west of Iran. Materials and Methods: The study was performed on urine and blood samples from kidney transplant ward, Golestan hospital, Ahvaz, Iran. To amplify the whole genome of BK polyomavirus AccuPower ProFi Taq PCR PreMix kit (Bioneer, South Korea) was used. Then, purified fragments were cloned into the vector. Sequences derived from the sequencing process were assembled by MEGA7 software. Data were analyzed using MEGA7 software and a phylogenetic tree was built based on the maximum likelihood ratio method. Results: Overall, 40 urine samples (40%) and two plasma samples (12%) were positive for BK virus DNA. For the selected samples, W.G. Long PCR was performed and 5.1 kbp fragment was observed in all five samples. These fragments were cloned and sequenced. Genomic sequence analysis of the 5 strains studied showed 97.6% homology and all our study samples were of the same clade, which could be a reason for our patients to be infected with the same strain. Comparing the 5 isolates in our study with reference strains, showed more than 98% of homology, and variation was observed in less than 2% of nucleotides. Conclusion: These five isolates showed more than 98% homology compared to the reference sequences, which can be attributed to the fact that these patients are infected with a common strain or that the genomic stability in the strain exists in our geographic area. We can conclude that in our geographic region there is a genomic stability and this strain can also be used as a positive control sample in other parts of the country